The Effects of a Green Nudge on Municipal Solid Waste: Evidence from a Clear Bag Policy - Mevlude Akbulut-Yuksel; Catherine Boulatoff (Institute of Labor Economics (IZA), 2020)
We explore the power of behavioral economic insights to influence the level of households' recycling and Municipal Solid Waste (MSW) by examining the effectiveness of a green nudge, the adoption of a Clear Bag Policy that was implemented in 2015 in a mid-size urban municipality in Canada. Using a Regression Discontinuity (RD) Design on universe administrative data, our analysis shows that this green nudge promoted recycling, and reduced both refuse and total MSW. While recycling increased by 15 percent, total MSW decreased by 27 percent overall between August 2015 and July 2017. Our results also demonstrate heterogeneity in response to a Clear Bag Policy across neighborhoods with varying socioeconomic indicators. Our findings suggest that green nudges can serve as effective policy instruments in devising future environment policies.
Keywords: D12; D91; H23; 330; environmental policy; green nudge; Municipal Solid Waste (MSW); regression discontinuity design; ArcGIS